Geogebra untuk Pengantar Pembelajaran Integral Tentu - Nalley, Nadya Gabriella; Katoda, Arcelia Grace Pora; Blegur, Irna Karlina Sensiana (Pendidikan Matematika FKIP Universitas Mataram, 2023)
Nowadays there are many technologies that can be utilized to support the educational process, including in the teaching of mathematics. In integral material, the usual approach involves explaining mathematical operations, giving an example, and doing the task. Students are not taught in-depth concepts about how integrals are obtained and the related issues with integrals. All of this could be due to the lack of use of media that supports stimulation and visualization of mathematics learning. One of the media that answers this problem is Geogebra. This article is a literature study that discusses the Geogebra application as an introduction to integral learning. Beside that, example of using Geogebra as a learning media to help students understand integral concepts are also presented.